Detection of HPV16 E6 DNA in periodontal pockets of middle‐aged and older people. Issue 1 (13th July 2020) - Shigeishi, Hideo; Murodumi, Hiroshi; Ohta, Kouji; Sugiyama, Masaru
Abstract: Background: This study was conducted to investigate the association between oral human papillomavirus type 16 (HPV16) DNA prevalence and periodontitis. Materials and Methods: We analyzed 89 patients (mean age 71.9 years, range 48‐90 years) who visited the Department of Oral Health of Hiroshima University Hospital. Samples were collected by inserting sterilized paper points into each patient's deepest periodontal pocket to obtain gingival crevicular fluid. Real‐time PCR was performed using type‐specific primers to detect HPV16 DNA. PCR‐targeted bacterial 16S rRNA genes were used to detect periodontal disease‐related bacteria. Results: Of the 89 participants, four women (4.5%) were HPV16 DNA‐positive. Three of the four HPV16 DNA‐positive participants (75.0%) exhibited bleeding after the paper point was inserted, indicating periodontal tissue inflammation. However, no significant association was found between bleeding and the HPV16 DNA‐positive rate. Importantly, HPV16 DNA positivity was significantly associated with Treponema denticola and Fusobacterium nucleatum ( P = 0.01 and P = 0.02, respectively). Conclusions: Human papilloma virus localizes in periodontal pockets. Inflamed periodontal pockets may indicate oral HPV infection. Periodontitis‐related bacteria may be involved in HPV infection of the periodontal tissues.